Cultural violence in the classroom : peace, conflict and education in Israel - Standish, Katerina (Peace Studies: Edges and Innovations., 2015)
In identity-based conflicts, what a person learns can become whom a person learns to hate. This book explores the unique position occupied by educators during protracted ethnic conflict. As transmitters of social authority, educators occupy a position in society capable of supporting repressive constructs or challenging social inequalities. Educators who are seen to legitimize the social order may be seen as symbolic markers of the dominant group, while educators who challenge the social order can be perceived as upstarts or threats that seek to subvert social authority. By surveying the percep.